1996
DOI: 10.1139/x26-023
|View full text |Cite
|
Sign up to set email alerts
|

Ecosystem nutrient responses to chronic nitrogen inputs at Fernow Experimental Forest, West Virginia

Abstract: Among the current environmental concerns for forests of the eastern United States is nitrogen (N) saturation, a result of excessive inputs of N associated with acidic deposition. We studied nutrient responses on N-treated and untreated watersheds of the Fernow Experimental Forest, West Virginia, to test for evidence of N saturation on the treated watershed. The watersheds were WS7 (23-year-old even-aged control), WS4 (mature mixed-aged control), and WS3 (23-year-old even-aged treatment). WS3 has received aeria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 113 publications
(46 citation statements)
references
References 29 publications
3
42
0
1
Order By: Relevance
“…For example, the Watershed Acidification Study at Fernow Experimental Forest, West Virginia, added 35 kg NÁha , which has led to changes in understory species composition . Recently, similar changes in understory species composition have occurred on the adjacent reference watershed receiving only ambient atmospheric deposition (Gilliam et al 1996;F. S. Gilliam, unpublished data) suggesting that the deposition to the reference watershed currently exceeds the critical load.…”
Section: Fig 4 Map Of (A) Critical Loads (Cl) and (B) Exceedances Omentioning
confidence: 75%
“…For example, the Watershed Acidification Study at Fernow Experimental Forest, West Virginia, added 35 kg NÁha , which has led to changes in understory species composition . Recently, similar changes in understory species composition have occurred on the adjacent reference watershed receiving only ambient atmospheric deposition (Gilliam et al 1996;F. S. Gilliam, unpublished data) suggesting that the deposition to the reference watershed currently exceeds the critical load.…”
Section: Fig 4 Map Of (A) Critical Loads (Cl) and (B) Exceedances Omentioning
confidence: 75%
“…Several previous studies (Stoddard 1994;Gilliam et al 1996;Peterjohn et al 1996) concluded that, in addition to WS3, which is the N-fertilized watershed, other watersheds at FEF are experiencing increasing levels of N saturation because of high levels of ambient atmospheric deposition. In comparison with our results, Gilliam et al (2001) …”
Section: Soil Nmentioning
confidence: 99%
“…Ecosystem-level responses to N saturation have been well documented (e.g., Tamm et al 1995;Gilliam et al 1996;Peterjohn et al 1996;Edwards et al 2002;Fernandez et al 2003), but there has been little study of the effects of excessive N deposition on internal plant nutrient dynamics or the potential for plants to modify those effects through variation in the disposition and use efficiency of individual nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Eastern hardwood forest regions with higher levels of N deposition (US EPA 2002; Experimental N additions indicate broadly similar responses to the gradient studies above ( (Gilliam et al 1996), and decreased tree growth by some species but not others (May et al 2005, DeWalle et al 2006. Th ese results resemble those from fertilization experiments at an oak stand at Millbrook, New York (Wallace et al 2007), and at a red pine stand and an oak-maple stand at Harvard Forest, Massachusetts (Table 10.1; Bowden et al 2004, Frey et al 2004, Magill et al 2000, Magill et al 2004, Minocha et al 2000, Venterea et al 2004.…”
Section: Range Of Responses Observedmentioning
confidence: 53%